Pengaruh non Performing Financing dan Financing to Deposit Ratio terhadap Pembiayaan pada Bank DKI Syariah - Najibullah Najibullah; Nurjaya Nurjaya (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of Non Performing Financing and Financing to Deposit Ratio on Financing at Bank DKI Syariah. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Non Performing Financing has a significant negative effect on financing by 54.9%, hypothesis testing obtained t count <t table or (-2.920 <2.365). Financing to Deposit Ratio has a significant negative effect on financing by 52.1%, hypothesis testing is obtained t count <t table or (-2,759 <2,365). Simultaneously Non Performing Financing and Financing to Deposit Ratio have a negative but insignificant effect on financing, the regression equation Y = 39.568 - 0.630X1 - 0.132X2 and a determination value of 57.9%, hypothesis testing obtained F value <F table or (4,110 <4,760).